2020
DOI: 10.1002/adsc.202000986
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Assisted, Photoredox/Cobalt Co‐catalyzed Semi‐Hydrogenation and Tandem Cyclization of o‐Alkynylphenols for Access to 2,3‐Dihydrobenzofurans

Abstract: Herein, a hydroxyl assisted, photoredox/cobalt co‐catalyzed semi‐hydrogenation and tandem cyclization of o‐alkynylphenols is developed towards direct assembly of 2,3‐dihydrobenzofurans. Moderate to good yields were obtained for a range of sterically and electronically diverse 2‐propynolphenols under mild conditions. Mechanistic studies demonstrated the inevitable role of the alcoholic hydroxyl group with (Z)‐alkene as the real intermediate. Finally, a key low‐valent cobalt catalyzed intramolecular hydroetherif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Meanwhile, we also conducted the experiments that using prepared (Z)‐ 8 and (E)‐ 8 as substrates under standard conditions, but none of reactions were occurred (Scheme S6). Since (Z)‐ 8 was proved to be an intermediate in our previous work (Scheme 1b), we thus deduced that this work should proceed via a highly different mechanism from our previous work [11] . Third, the light on/off experiment was conducted (Figure 1b).…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…Meanwhile, we also conducted the experiments that using prepared (Z)‐ 8 and (E)‐ 8 as substrates under standard conditions, but none of reactions were occurred (Scheme S6). Since (Z)‐ 8 was proved to be an intermediate in our previous work (Scheme 1b), we thus deduced that this work should proceed via a highly different mechanism from our previous work [11] . Third, the light on/off experiment was conducted (Figure 1b).…”
Section: Methodsmentioning
confidence: 85%
“…We started to verify our hypothesis by using similar conditions in our previous work, [11] that is, selecting 1 a as the model substrate, Ir[dF(CF 3 )ppy] 2 (dtbbpy)PF 6 as photocatalyst, 4,4′‐di‐tert‐butyl‐2,2′‐bipyridine ( L1 ) as ligand, and i ‐Pr 2 NEt as radical sacrificial in n ‐propyl alcohol at room temperature (table 1, entry 1). Unfortunately, none of corresponding benzo[ b ]furan 2 a was detected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, the research group of Qiang Xiao illustrated the hydroxyl assisted photoredox/cobalt Co-catalyzed semi-hydrogenation and tandem cyclization of o-alkynylphenols 65 for the synthesis of 2,3-DHBs 66. [101] In this context, an efficient catalytic system has been established using 2-propynolphenols 65 as a substrate in the presence of blue LED irradiation at ambient temperature (Scheme 15). It was observed that the alcoholic hydroxyl group played an essential role in the reaction, and (Z)alkene 67 was the intermediate for the conversion.…”
Section: Photoredox/cobalt Co-catalyzed Synthesis Of 23-dihydrobenzof...mentioning
confidence: 99%